Effect of thermal cycling and disinfection on microhardness of acrylic resin denture base - Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP]; Baptista, Gabriella Trunckle [UNESP]; Moreno, Amália [UNESP]; Andreotti, Agda Marobo [UNESP]; Dekon, Stefan Fiuza de Carvalho [UNESP] (Taylor & Francis, 2013)
The purpose of this study was to investigate the effect of thermal cycling and disinfection on the microhardness of acrylic resins denture base. Four different brands of acrylic resins were evaluated: Onda Cryl, QC 20, Classico and Lucitone. Each brand of acrylic resin was divided into four groups (n = 7) according to the disinfection method (microwave, Efferdent, 4% chlorhexidine and 1% hypochlorite). Samples were disinfected during 60 days. Before and after disinfection, samples were thermal cycled between 5-55 °C with 30-s dwell times for 1000 cycles. The microhardness was measured using a microhardener, at baseline (B), after first thermal cycling (T1), after disinfection (D) and after second thermal cycling (T2). The microhardness values of all groups reduced over time. QC-20 acrylic resin exhibited the lowest microhardness values. At B and T1 periods, the acrylic resins exhibited statistically greater microhardness values when compared to D and T2 periods. It can be concluded that the microhardness values of the acrylic resins denture base were affected by the thermal cycling and disinfection procedures. However, all microhardness values obtained herein are within acceptable clinical limits for the acrylic resins. © 2013 Informa UK Ltd.
Keywords: Acrylic resins; Ageing; Disinfection; Hardness; Chlorhexidine; Denture base; Disinfection methods; Dwell time; Four-group; Microhardness; Thermal cycling; Resins; acrylic acid resin; chlorhexidine; hypochlorite; cycling; denture base; disinfection; microwave radiation